Maranatha our Lord come a definative study of the rapture of the church - Showers, Renald E. (Bellmawr, NJ The Friends of Israel Gospel Ministry, 2002)
Contents : Part 1: Preliminsry considerations : The birth pangs of the Messiah; The biblical concepy of the Day of the Lord; The Day of the Lord, the time of Jacob's trouble and the Great Tribulation; The end and beginning of the beginning judgement phase of the future Day of the Lord; The sealed scroll of Revelation 5; Observations related to the seals. Part 2 : Biblical inferences for the Pretribulation Rapture of the church : The imminent coming of Christ; Behold the Bridegroom comes; The Rapture and the coming of Christ with his holy angels; The relationship of church saints to the wrath of God; The request to the troubled Thessalonians; The seventy-weeks prophecy of Daniel 9; The references to the church and Israel in the book of Revelation. Conclusion : So what? Addendum : What about the last trump? Includesbibliographical references and indexes.
Keywords: Eschatology; Rapture -- biblical teaching